Penerapan Promotion Mix pada Kedai Kopi di Saat Pandemi Covid-19 - Wisnu Yuwono; Noveldi Oktovian (ConCEPt - Conference on Community Engagement Project, 2021)
The purpose of this community service activity is to implement the promotion mix program in order to increase the number of customers, increase income, and expand public knowledge about Time To Eat coffee shop located at Ruko Eden Park Blok D No. 15-16, Batam Center, Batam. The method of implementing the activity is divided into several stages, namely the preparation, the observation stage, the data collection stage, the problem identification stage, the marketing strategy design stage, the implementation stage, and the evaluation stage. The results of the activity show that the program has been running effectively with the addition of 10% new customers and an increase in sales turnover. It is recommended that partners use the results of this design optimally and consistently if they want to develop further.